Wits Architecture Student Works 1922-1980; CT1, CT2, CT3 - Student Work (My University, 2014)
Wits Architecture Student Works 1922-1980; CT1 Layout Plan, CT2 Plan of Skyscrapers, CT3 Circulation with key rail, tube, bus & service; Cape Town Urban Design
Wits Architecture Student Works 1922-1980; CT1 Layout Plan, CT2 Plan of Skyscrapers, CT3 Circulation with key rail, tube, bus & service; Cape Town Urban Design
Keywords: Wits Architecture Student Works 1922-1980; CT1 Layout Plan, CT2 Plan of Skyscrapers, CT3 Circulation with key rail, tube, bus & service; Cape Town Urban Design